Organización Contable en la Empresa Inmobiliaria Loja de la ciudad de Loja del periodo del 01 de abril al 30 de junio del 2022 - Puchaicela Robalino, Rosa Katherine (2023)
This thesis entitled, Accounting organization in the Loja real estate company in the city of Loja, period from April 1 to June 30, 2022, was developed with the purpose of proposing instruments that provide the owner with accounting information that allows knowing the financial situation. and economic of the company and in this way make decisions. To fulfill each of the specific objectives, it began with an analysis of the activities carried out by the Real Estate Company, thus allowing the physical verification of the assets it owns, designing a plan and account manual according to the needs of the company same as it is ordered and coded numerically presenting the accounts of the assets, liabilities, equity, income and expenses, following this we proceeded with the collection and organization of the source documentation provided to us by the owner, the initial inventory was carried out. , which helped with the preparation of the initial balance sheet that determines the assets, liabilities and equity, in order to begin with the respective accounting record, the auxiliary books of sales, accounts receivable, accounts payable, depreciation, fuel, payment roles and provisions to proceed to record the operations in the journal that has the respective adjusting and closing entries, with this information the general ledger, trial balance, work sheet was prepared up to the presentation of the Financial Statements with their respective explanatory notes, where the statement of financial position reflects a total of assets of $92,557.04, total liabilities of $21,033.00 and equity of $71,523.82; the income statement with total income of $3,758.17 and expenses of $3,721.32; having a profit of $36.85; and finally the cash flow statement having a total of cash received per client of $5,256.1, the net cash flow from operating activities of $2,257.48, the total cash from financing activities $20,339.79 and the cash and Its cash equivalents at the beginning of the period were $3,250.00, having a final result at the end of the period of $26,588.48. Once the degree work is completed, it is determined that accounting implementation is of great importance since it allowed to establish an adequate organization of economic activities, obtaining clear and orderly information reflected in the financial statements, thus allowing its manager-owner to know the reality of the business economy and thus be able to make the right decisions for real estate.